Transformasi Transaksi Keuangan Digital: Pengaruh Penggunaan Sistem Pembayaran Non-Tunai terhadap Kinerja Keuangan UMKM di Kabupaten Pamekasan - Fadhoilus Shofi; Wahyu Agung Setio Prabowo; Amalia Rosada (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the effect of non-cash payment systems on the financial performance of food and beverage MSMEs in Pamekasan Regency. The research background highlights the growing digitalization of transactions through QRIS, digital wallets, and mobile banking, prompting MSME actors to adopt more efficient, secure, and documented payment methods. A quantitative explanatory approach was employed, using purposive sampling to select 110 MSME owners who had utilized non-cash payments for at least one year. Primary data were collected via Likert-scale questionnaires, and analysis involved validity and reliability tests, classical assumption tests, and simple linear regression. The findings indicate that non-cash payments positively and significantly influence MSME financial performance, with a regression coefficient of 0.137, a significance value of 0.000, and an R Square of 0.308. This suggests that non-cash payment adoption accounts for 30.8% of the variance in MSME financial performance, while 69.2% is explained by other factors outside the model. The results demonstrate that non-cash payments not only function as alternative transaction methods but also enhance financial management, accelerate transactions, increase customer trust, and support improvements in sales, profit, and business assets. The findings theoretically reinforce the Technology Acceptance Model, Diffusion of Innovation, and Resource-Based View, highlighting the crucial role of digital capabilities in enhancing MSME performance. The study implies that integrating non-cash payments into daily operations can serve as a strategic tool for financial management and competitiveness in the digital economy era.